2008
DOI: 10.1093/aje/kwn286
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence in the United States of Selected Candidate Gene Variants: Third National Health and Nutrition Examination Survey, 1991-1994

Abstract: Population-based allele frequencies and genotype prevalence are important for measuring the contribution of genetic variation to human disease susceptibility, progression, and outcomes. Population-based prevalence estimates also provide the basis for epidemiologic studies of gene–disease associations, for estimating population attributable risk, and for informing health policy and clinical and public health practice. However, such prevalence estimates for genotypes important to public health remain undetermine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
96
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 75 publications
6
96
1
Order By: Relevance
“…9 The F5 variant is virtu ally absent in native Asian and African populations, and F2 is rare. 8,10 Individuals having two copies of the F5 or F2 variants (approximately 1 in 1,000 and <1 in 8,000 whites, respectively), review or one of each variant, are much less common.…”
Section: Genet Med 2012:14(1):39-50mentioning
confidence: 99%
See 1 more Smart Citation
“…9 The F5 variant is virtu ally absent in native Asian and African populations, and F2 is rare. 8,10 Individuals having two copies of the F5 or F2 variants (approximately 1 in 1,000 and <1 in 8,000 whites, respectively), review or one of each variant, are much less common.…”
Section: Genet Med 2012:14(1):39-50mentioning
confidence: 99%
“…8,10 Individuals having two copies of the F5 or F2 variants (approximately 1 in 1,000 and <1 in 8,000 whites, respectively), review or one of each variant, are much less common. 9 A thrombotic pathogenesis for pregnancy loss proposes that one or two cop ies of these variants could enhance the existing hypercoagulable state in pregnant women and that impaired fetal circulation or thrombotic vasculopathy in the placenta could result in placen tamediated pregnancy complications and fetal loss. 3,4,11,12 F5 and F2 are the most frequently ordered genetic variants associated with RPL 13,14 but does the accumulated knowledge base support the broadbased use of these tests to screen women with RPL to identify those who may benefit from specific man agement or treatment?…”
Section: Genet Med 2012:14(1):39-50mentioning
confidence: 99%
“…The authors found significant differences in allele frequency (in 88 of 90 genetic variants) and genotype prevalence (in 87 of 90 genetic variants). 5 Non-Hispanic blacks had considerable differences in minor allele frequency compared with nonHispanic whites, with almost one-quarter of variants differing by at least 20% (absolute difference). 5 Ioannidis et al 6 assessed 43 meta-analyses of gene-disease associations from the candidate gene era across 697 study populations of various ethnicities and found that frequencies of polymorphisms in seven cardiovascular disease genes varied significantly between ethnicities.…”
Section: Introductionmentioning
confidence: 98%
“…5 Non-Hispanic blacks had considerable differences in minor allele frequency compared with nonHispanic whites, with almost one-quarter of variants differing by at least 20% (absolute difference). 5 Ioannidis et al 6 assessed 43 meta-analyses of gene-disease associations from the candidate gene era across 697 study populations of various ethnicities and found that frequencies of polymorphisms in seven cardiovascular disease genes varied significantly between ethnicities. However, they observed large heterogeneity in the genetic effects (odds ratios) between ethnicities in only 14% of the cases indicating that their biological impact on the risk for common diseases may usually be consistent across traditional 'racial' boundaries.…”
Section: Introductionmentioning
confidence: 98%
“…More details on the construction of the GRS are available in the online-only Data Supplement. 28,29 Allele frequencies were calculated and weighted using NHANES III sample weights for each variant, stratifying by racial/ethnic group. Racial/ethnic differences in allele frequencies were tested in pooled data from all racial/ethnic groups using the Satterthwaite-adjusted F test in polytomous logistic regression.…”
mentioning
confidence: 99%